The Crisis of Accountability in Indonesia Education Performance Amid Low PISA Results: An Analysis of UNESCO Framework to Enhance National Competitiveness - Rahmadani Fitri; Rabukit Damanik; Berliani Ritonga; Zainuddin; Rahmat Hidayat (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
Indonesia low performance in the Programme for International Student Assessment (PISA) raises serious questions about the effectiveness of the national education performance accountability system. This article analyzes the relationship between PISA outcomes and the crisis of educational accountability by using the UNESCO accountability framework as an analytical lens. A conceptual-analytical approach is employed to examine how monitoring systems, evaluation practices, data transparency, and continuous improvement mechanisms have not yet functioned optimally in Indonesia. The findings reveal policy fragmentation, weak data utilization, and a gap between national assessments and international competency standards. The UNESCO framework offers a holistic approach grounded in quality, equity, and collaboration that can strengthen education governance. This article recommends aligning national assessments with PISA competencies, strengthening data-driven accountability, improving the quality of teachers’ pedagogy, and ensuring long-term policy consistency as strategies to enhance Indonesia’s educational competitiveness.